2021
DOI: 10.1371/journal.pntd.0009159
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study to evaluate the accuracy of rapid diagnostic tests for diagnosis of human leptospirosis: Result from THAI-LEPTO AKI study

Abstract: Background Rapid diagnostic tests (RDTs) have become widely used in low-resource settings for leptospirosis diagnostic. This study aims to evaluate the diagnostic performance of the five commercially available RDTs to detect human IgM against Leptospira spp. in Thai population. Methodology/Principal findings Ninety-nine serum samples from Leptospirosis suspicious patients were tested with five RDTs, including Medical Science Public Health, Leptocheck-WB, SD bioline, TRUSTline, and J.Mitra. The case definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 19 publications
(17 reference statements)
3
30
0
Order By: Relevance
“…IgM antibodies. The RDT performance was similar to that previously reported [ 9 ], but had a lower sensitivity, specificity, and accuracy than the RPA-CRISPR/Cas12a-FBDA developed in this study. The window of positivity for the RPA-CRISPR/Cas12a platform began at the first sign of infection, compared to the RDT window which started at days 6–8 [ 5 , 36 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…IgM antibodies. The RDT performance was similar to that previously reported [ 9 ], but had a lower sensitivity, specificity, and accuracy than the RPA-CRISPR/Cas12a-FBDA developed in this study. The window of positivity for the RPA-CRISPR/Cas12a platform began at the first sign of infection, compared to the RDT window which started at days 6–8 [ 5 , 36 ].…”
Section: Discussionsupporting
confidence: 87%
“…Results from our study support usage of the RPA-CRISPR/Cas12a-based system to detect Leptospira with an acceptable sensitivity and high specificity. To address the sensitivity and specificity issues raised by prior studies, point-of-care testing for leptospirosis such as LAMP and RDT were created [ 9 , 10 ]. A previous study reported that having more than 1,000 Leptospira cells/mL was associated with severe leptospirosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations